Stereoselective Synthesis of 4-Substituted 2,4-Dichloro-2-butenals by α- and γ-Regioselective Double Chlorination of Dienamine Catalysis - Arimitsu, Satoru; Terukina, Kazuto; Ishikawa, Tatsuro (Synlett, 2018)
The l-proline-catalyzed reaction of enolizable α,β-unsaturated aldehydes with N-chlorosuccinimide (NCS) gave the corresponding 4-substituted 2,4-dichloro-2-butenals with moderate yields and excellent diastereoselectivities (Z/E = >20/1) through consecutive double chlorination at the α- and γ-positions of the dienamine intermediate. The corresponding 2,4-dichloro-2-butenals contain a multireactive 1,3-dichloro allylic unit useful for the construction of Z-vinyl chlorides; the chloride on the allylic position was replaced with mild nucleophiles such as MeOH and EtOH via an SN2 substitution reaction, and its aldehyde moiety was used as a synthetic handle and transformed into an alcohol or a vinyl group. All products obtained after those synthetic manipulations maintained excellent diastereoselectivities (Z/E = >20/1).
Keywords: 2,4-dichloro-2-butenals; dienamine catalysis; chlorination; stereoselective; regioselective